Flexural behavior of UHPC beam reinforced with steel-FRP composite bars. (June 2022) - Abbas, Ebrahim M.A.; Ge, Yue; Zhang, Zhiwen; Chen, Yiwen; Ashour, Ashraf; Ge, Wenjie; Tang, Rong; Yang, Zhongping; Khailah, Ebrahim Y.; Yao, Shan; Sun, Chuanzhi
Abstract: This paper numerically investigates flexural performance of Ultra-High Performance Concrete (UHPC) beam reinforced with Steel-Fibre-Reinforced Polymer (FRP) Composite Bars (SFCBs) in terms of flexural stiffness, moment capacity, deflection, ductility and energy dissipation. The effect of various parameters, include the inner steel core area ratio of SFCB, yield strength of inner steel core, elastic modulus and ultimate strength of outer-wrapped FRP, reinforcement ratio, type and strength of concrete were studied. The results demonstrate that the inner steel core area ratio of SFCB, reinforcement ratio and the elastic modulus of SFCB's outer FRP have significant effect on the overall flexural performance of SFCB reinforced UHPC beam. The overall flexural performance of SFCB reinforced UHPC beam is slightly improved by increasing the yield strength of inner steel core of SFCB, but not affected by the ultimate strength of SFCB's outer FRP when specimen occurred compression failure. The results also exhibit that the flexural performance of UHPC beam reinforced with SFCBs is significantly improved when compared to those of reinforced high strength concrete (HSC) beam and normal strength concrete (NSC) beam. The flexural stiffness and the moment capacity of SFCB reinforced UHPC beam at the ultimate point were 2.0 and 2.4 times, respectively, of those of reinforced NSC counterpart.